A 4-D discrete cosine transform-based light field coding solution - Alves, Gustavo de Oliveira e (2019)
It is well known that the conventional ways to capture the light around us are limited and thus provide a limited user experience, notably in terms of parallax capabilities. As this has been preventing 3D systems to explode in the market, significant advances are emerging in terms of light capturing technologies among which is relevant to highlight the so-called light field cameras which capture a richer representation of the visual scene by measuring the light intensity for each direc- tion and for each pixel position. Considering the huge amount of light intensity data involved, e cient compression becomes a must. In this context, this disser- tation addresses the light field coding challenge by proposing a 4D discrete cosine transform-based coding solution. The DCT is an natural candidate to this kind of processing considering its wide adoption in conventional image and video coding standards.